Diaphragm disease in advanced ovarian cancer: Predictability of pre-operative imaging and safety of surgical intervention. (July 2018) - Pounds, Rachel; Phillips, Andrew; Kehoe, Sean; Nevin, James; Sundar, Sudha; Elattar, Ahmed; Teo, Hong Giap; Singh, Kavita; Balega, Janos
Abstract: Objectives: To establish the positive predictive values of pre-operative identification with CT imaging of metastatic diaphragm disease in surgically managed cases of advanced ovarian cancer (AOC). Additionally, we have assessed the post-operative morbidity and survival following diaphragmatic surgical intervention in a large regional cancer centre in the United Kingdom. Study design: A retrospective review of all cases of AOC with metastatic diaphragm disease surgically treated at the Pan-Birmingham Gynaecological Cancer Centre, UK between 1st August 2007 and 29th February 2016. Results: A total of 536 women underwent surgery for primary AOC. Diaphragm disease was evident intra-operatively in 215/536 (40.1%) and 85/536 women (15.9%) underwent a procedure involving their diaphragm. Of these 85 cases, 38 peritoneal strippings (38/85, 44.7%), 31 partial diaphragmatic resections (31/85, 35.6%) and 16 electro-surgical ablations (16/85, 18.9%) were performed. There were no significant differences in post-operative complications between the three different diaphragmatic surgical groups. Of those patients who underwent peritoneal stripping or partial diaphragm resection, 12% were upstaged to stage 4A by virtue of pleural invasion. The positive predictive value for pre-operative radiological identification of diaphragmatic disease was 78.6%. CT imaging failed to detect diaphragmatic involvement despite obvious diaphragm disease during surgery in 29.4% of cases, giving a low negative predictive value of 64.8%. The sensitivity and specificity for CT imaging in detecting diaphragm disease was 44.3% and 93.8%, respectively. Conclusions: Diaphragmatic disease is often discovered in AOC. However, pre-operative assessment with CT imaging is not reliable in accurately detecting diaphragm involvement. Therefore, all patients with AOC should be regarded as in potential need for diaphragm surgery and their operation undertaken in cancer centres with adequate expertise in upper abdominal surgery. If there is a suspicion of diaphragm muscle invasion during diaphragmatic peritonectomy, the muscle should be partially resected. This will lead to potential upstaging of disease to stage 4A and therefore, to suitability for targeted therapy. In our Centre, the surgical removal of diaphragmatic disease did not significantly increase surgical morbidity.